Recuperação de solo em processo de arenização com o uso de espécies vegetais em pomar de amoreira-preta - Machado, Jéssica Cristine Viera (2012)
The southwest region of Rio Grande do Sul (RS) state has widespread areas with sandy soils in the process of sandification. In the present study, we report the effect of different intercropping in blackberry plants on the soil recuperation and crop productivity. The experiment was conducted in São Francisco de Assis located in southwest region of the RS. The soil was a typical Psament with 60 g kg-1 clay and 0.5 g kg-1 organic matter in the top 0- 10 cm layer. The crops that were intercropped with blackberry were jack bean (Canavalia ensiformis) / oat (Avena strigosa) (JB-O); Brachiaria (Brachiaria decumbens) (BRA) and native grass (NG). The soil recuperation was measured by assessing the C and N stocks in the soil and biological indicators such as the enzymatic activity and soil fauna in relation to traditional grazing native grass (GNP). Results showed that intercropping of crops with blackberry improved soil biological conditions in relation to the GNP. Intercropping of JB-O with blackberry resulted in high dry matter production and C and N accumulation in shoots. Similarly, among the crops BRA appeared to be the crop that has potential to increase C and N stocks in the soils. This effect could be explained the rooting system of this grass. The presence of NG under blackberry helped to achieve average fruit yield and could be used as a strategy to establish the cultivation of blackberry in this region. Moreover, blackberry showed adaptation to the ecological conditions of the sandy soils and can be considered as an alternative crop for 1) recovering and reducing the outspread of sandification 2) as a possible source of income for the farmers of this region.